Facile assembly of TiO2 nanospheres/SnO2 quantum dots composites with excellent photocatalyst activity for the degradation of methyl orange. Issue 11 (15th August 2016) - Du, Feng; Zuo, Xueqin; Yang, Qun; Yang, Bo; Li, Guang; Ding, Zongling; Wu, Mingzai; Ma, Yongqing; Jin, Shaowei; Zhu, Kerong
Abstract: In this report, SnO2 quantum dots anchored on TiO2 nanospheres (TiO2 /SnO2 composites) have been synthesized by a simple one-step hydrothermal process, and then employed as photocatalyst in photodegradation system. The microstructure of TiO2 /SnO2 composites reveals that the SnO2 quantum dots are dispersed on the surface of TiO2 nanospheres uniformly. The photocatalytic behavior of the as-prepared samples revealed that the composites exhibited highly efficient performance by degrading 100 mL of 10 mg/L methylene orange in 15 min completely under ultraviolet-visible light. Owning to the special structure of the composites, TiO2 /SnO2 shows a more UV–vis light absorption than either pure TiO2 nanospheres or pure SnO2 quantum dots. This study offers a facile method to prepare TiO2 /SnO2 composites, which will be a choice for greatly extending potential applications in water pollution treatment, degradation of pollutants and other related fields.